Progressive structuring of a branched antimicrobial peptide on the path to the inner membrane target - Beuerman, Roger W. (2013)
In recent years, interest has grown in the antimicrobial properties of certain natural and non-natural peptides. The strategy of inserting a covalent branch point in a peptide can improve its antimicrobial properties while retaining host biocompatibility. However, little is known regarding possible structural transitions as the peptide moves on the access path to the presumed target, the inner membrane. Establishing the nature of the interactions with the complex bacterial outer and inner membranes is important for effective peptide design. Structure-activity relationships of an amphiphilic, branched antimicrobial peptide (B2088) are examined using environment-sensitive fluorescent probes, electron microscopy, molecular dynamics simulations, and high resolution NMR in solution and in condensed states. The peptide is reconstituted in bacterial outer membrane lipopolysaccharide extract as well as in a variety of lipid media mimicking the inner membrane of Gram-negative pathogens. Progressive structure accretion is observed for the peptide in water, LPS, and lipid environments. Despite inducing rapid aggregation of bacteria-derived lipopolysaccharides, the peptide remains highly mobile in the aggregated lattice. At the inner membranes, the peptide undergoes further structural compaction mediated by interactions with negatively charged lipids, probably causing redistribution of membrane lipids, which in turn results in increased membrane permeability and bacterial lysis. These findings suggest that peptides possessing both enhanced mobility in the bacterial outer membrane and spatial structure facilitating its interactions with the membrane-water interface may provide excellent structural motifs to develop new antimicrobials that can overcome antibiotic-resistant Gram-negative pathogens.